VALIDITAS E-LKPD INTERAKTIF MENGGUNAKAN LIVEWORKSHEET PADA MATERI IKATAN KIMIA BERBASIS INKUIRI TERSTRUKTUR UNTUK FASE F SMA - Fatimah Az Zahra; Minda Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Chemical bonding is a fundamental chemistry topic that is complex and abstract, making it difficult for students to understand. This study aimed to develop a valid interactive electronic student worksheet (E-LKPD) using Liveworksheet on chemical bonding based on the structured inquiry approach. This study employed the Educational Design Research (EDR) method using the Plomp model, which consists of the preliminary research, prototyping, and assessment phases. The study was limited to the prototyping phase up to Prototype III. The research instrument was a validation questionnaire completed by three validators. The validation data were analyzed using Aiken's V coefficient, with an average value of 0,95. The results showed that the interactive E-LKPD using Liveworksheet on chemical bonding based on the structured inquiry approach for Phase F senior high school students was valid.